Rock Displacement at Underground Coal Gasification - V. R., Kadirov; Y. T., Nurboboev; A. A., Umirzoqov; Elbek, Muhammadiyev (International Journal of Human Computing Studies, 2022)
In this article the process of underground coal gasification, its impact to the rock displacement and methods for controlling the roof stability is described.